The possibilities of academic disciplines in introducing students of a technical university to moral values - Oksana K. Pozdnyakova; Elena I. Soboleva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper presents the study on the problem of the formation of the personality of a student a future engineer as a moral person, an aspect of which is the definition of the value content of academic disciplines studied at a technical university, and the implementation of this content in the moral education of students. The relevance of the study is determined by the fact that the formation of a student as a moral person is associated with the rooting in his mind of moral values, which are reflected in the value orientations of the future engineer. As a mechanism for the formation of students value orientations, they are introduced to values. The purpose of the study is to identify the possibilities of academic disciplines studied at a technical university in introducing students to moral values. In the course of the study, an analysis was made of the content of the Federal State Educational Standard of Higher Education in the direction of training 21.03.01 Oil and Gas Business, the training profile Operation and maintenance of oil production facilities, as well as the content of the curriculum for this profile of training, on the basis of which academic disciplines were determined, on which it is possible introducing students to moral values: History, Philosophy, Foreign language, Jurisprudence, Theory and practice of social communications, Ecology, Life safety, Physics, Chemistry, History oil and gas industry, Geology and lithology. Based on the analysis of work programs in academic disciplines and comparison of program materials with scientific knowledge about moral values, the content and procedural aspects of introducing students to moral values are revealed. Specific examples show the possibilities of the disciplines Jurisprudence, Theory and practice of social communications, Ecology, Life safety, Physics in introducing students to moral values. Based on the results of the study, conclusions were drawn, firstly, about the uneven reflection of moral values that determine the relationship engineer colleagues, engineer technology (technosphere), engineer society in the content of disciplines; secondly, about the possibility of using common methods and means to familiarize students with moral values in the classroom in various academic disciplines conversation, discussion, dispute, business game, role-playing game.